Mechanical Properties of Coconut Shell Lightweight Aggregate Concrete: A Comprehensive Review - Alireza Javadi Pordesari; Payam Shafigh; Muhammed Talha Ünal; Zainah Ibrahim (Advances in Civil Engineering)
Using agricultural wastes as construction materials for environmentally friendly construction offers practical and economic advantages. Several types of agricultural wastes have been researched and proposed to the industry for sustainable construction. Coconut shell (CS), a by-product of extracting coconut oil or milk, has been the focus of research over the past two decades. Researchers have used it as an aggregate in concrete mixtures. This article provides a comprehensive review of previous research on the properties of CS as an aggregate and its influence on the mechanical properties of concrete, compared to normal weight and other types of lightweight concretes. Researchers revealed that CS is a porous material with a specific gravity ranging from 1.03 to 1.56, which is significantly less than conventional aggregates. CS aggregate is composed of a hard and fibrous material, making it durable, strong, and flexible. When used as a coarse lightweight aggregate (fully or partially) in concrete mixtures, a concrete with a density ranging from 1445 to 2530 kg/m³ and a compressive strength of 5–56 MPa can be produced. The optimal contribution rates of CS as coarse aggregate in concrete to achieve desired mechanical properties range between 20% and 50%. However, higher CS content poses challenges to workability and leads to a low modulus of elasticity. The application of pozzolanic materials in the range of 20%–30%, along with a superplasticizer, can significantly improve the overall properties of CS concrete in both fresh and hardened states. It is also suggested that adding fibers at a volume fraction of 0.5%–1.0% can substantially increase the tensile and flexural strengths of CS concrete while improving its cracking and impact resistance.